The Case for Abandoning Therapeutic Chelation of Copper Ions in Alzheimer's Disease - Drew, Simon C. (Frontiers in Neuroscience, 2017)
The ‘therapeutic chelation’ approach to treating Alzheimer’s disease (AD) evolved from the metals hypothesis, with the premise that small molecules can be designed to prevent transition metal-induced amyloid deposition and oxidative stress within the AD brain. Over more than twenty years, countless in vitro studies have been devoted to characterizing metal binding, its effect on Aβ aggregation, ROS production and in vitro toxicity. Despite a lack of evidence for any clinical benefit, the conjecture that therapeutic chelation is effective approach for treating AD remains widespread. Here, the author plays the devil’s advocate, questioning the experimental evidence, the dogma and the value of therapeutic chelation, with a major focus on the role of copper ions.